Nicotinamide mononucleotide alters mitochondrial dynamics by SIRT3‐dependent mechanism in male mice. Issue 8 (23rd February 2019) - Klimova, Nina; Long, Aaron; Kristian, Tibor
Abstract: Nicotinamide adenine dinucleotide (NAD + ) is a central signaling molecule and enzyme cofactor that is involved in a variety of fundamental biological processes. NAD + levels decline with age, neurodegenerative conditions, acute brain injury, and in obesity or diabetes. Loss of NAD + results in impaired mitochondrial and cellular functions. Administration of NAD + precursor, nicotinamide mononucleotide (NMN), has shown to improve mitochondrial bioenergetics, reverse age‐associated physiological decline, and inhibit postischemic NAD + degradation and cellular death. In this study, we identified a novel link between NAD + metabolism and mitochondrial dynamics. A single dose (62.5 mg/kg) of NMN, administered to male mice, increases hippocampal mitochondria NAD + pools for up to 24 hr posttreatment and drives a sirtuin 3 (SIRT3)‐mediated global decrease in mitochondrial protein acetylation. This results in a reduction of hippocampal reactive oxygen species levels via SIRT3‐driven deacetylation of mitochondrial manganese superoxide dismutase. Consequently, mitochondria in neurons become less fragmented due to lower interaction of phosphorylated fission protein, dynamin‐related protein 1 (pDrp1 [S616]), with mitochondria. In conclusion, manipulation of mitochondrial NAD + levels by NMN results in metabolic changes that protect mitochondria against reactive oxygen species and excessive fragmentation, offering therapeutic approaches for pathophysiologic stress conditions. Abstract : NMN administration increases mitochondrial NAD + pools and drives the reduction of mitochondria generated ROS via a SIRT3‐dependent deacetylation and stimulation of SOD2 activity. As a result, fission is less active due to decreased binding of pDrp1 (S616) to the mitochondrial outer membrane.